Functional and Radiological Outcomes with Intramedullary Interlocking Nailing of Tibial Shaft Fracture - Kushwaha, Mukesh Prasad; Mourya, Vandana (Med Phoenix, 2022)
Introduction: Tibia is the most common long bone involved in fracture during Road Traffic Accident (RTA) because of its subcutaneous location. Intramedullary nail fixation remains the treatment of choice for unstable and displaced tibial shaft fractures in the adult. The goals of surgical treatment are to achieve osseous union and to restore length, alignment, and rotation of the fractured tibia. Intramedullary nailing carries the advantage of minimal surgical dissection with appropriate preservation of blood supply to the fracture site. Materials and Methods: This is a prospective observational study conducted in the Department of Orthopedics, National Medical College and Teaching Hospital,Birgunj, Parsa, Nepal for the 1 year duration. Patients included in this study were above 16 years with Tibia shaft fracture with or without fibula fracture which includes Type I,II and IIIA of Gustilo-Anderson fracture. Patients with tibia shaft fracture were treated surgically by using intramedullary interlocking nail then follow up done in OPD at regular intervals during which radiographs was taken in appropriate views and diagnosis is established by functional and radiological means. Result: Out of 53 patients, 45 patients with Tibia shaft fracture are treated by closed intramedullary interlocking nailing in the National Medical College, Birgunj. Eight patients are lost during follow-up. In our study tibia shaft Fracture was more common in male (77.8%) than female which mostly involved 18-30 years of age group (62.2%) and most common cause was Road Traffic Accident (82.2%). Thirty cases (66.7%) had excellent and 10 cases (22.2%) had good healing and complication were seen in eight patients (17.7%). Conclusion: Closed interlocking tibia nailing allows earlier fracture union with less morbidity. Because of the high union rate and low infection rate, we consider closed interlocking nailing as the best mode of treatment for diaphyseal tibial fractures.